Uma história do curso de Ciências Biológicas na Universidade Federal de Sergipe : para quê? o quê? para quem? como? (1969-1983). - Carmo, Kátia de Araújo (2011)
This study proposes a reflection about the meaning of the course of Biological Sciences, Universidade Federal de Sergipe, guided by the panorama educational, social and economic status. In this thesis, we investigated whether there was demand for biologists in the State of Sergipe, from the existing options for performance of these professionals; as well as the choices curriculum that contributed to the development of the identities of the trainees in the course of Biological Sciences at the UFS. The temporal march worked was the 1969 to 1983. The theoretical framework chosen was Bourdieu (1974; 2004), with the use of categories of Field and Scientific Capital; in addition, Silva (2011), with the categories of Curriculum and Identity; Chartier (1990), with Representation and Thompson (1992), with the concept of Oral History. The various sources used were: oral testimony, the minutes, the decrees, the photographs, reports, laws and trades. This study will contribute to the research on the History of Higher Education in territory Sergipe who.